Al-Hadith: Kedudukan dan Peranannya dalam Islam - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 1996)
The study which is attempt to elaborate the position and role of al-Hadith in Islam. The discussion is based on al-Qur’an, al-Hadith and the views of the authoritative ulama. In the discussion an attempt is also made to elaborate the meaning of al-Hadith from various aspects and disciplines.